Sequential Pd0‐ and PdII‐Catalyzed Cyclizations: Enantioselective Heck and Nucleopalladation Reactions. (9th August 2021) - Whyte, Andrew; Bajohr, Jonathan; Arora, Ramon; Torelli, Alexa; Lautens, Mark
Abstract: An enantioselective consecutive cyclization/coupling process, catalyzed by palladium is reported. Stereoinduction arises from an enantioselective carbopalladation, generating an intermediate which promotes a nucleopalladation step. The dual cyclization sequence was compatible with a variety of alkyne‐tethered oxygen‐ and nitrogen‐centered nucleophiles, and a variety of alkenyl‐tethered aryl iodides, to forge numerous bisheterocycles in good yields and high regio‐ and enantioselectivities. Abstract : The successive cyclization and cross‐coupling of alkenyl aryl iodides and alkyne‐appended nucleophiles via an enantioselective domino‐Heck and regioselective nucleopalladation is reported. Heterocycles originated from N ‐ or O ‐centered nucleophiles were successful in conjunction with the enantioselective formation of dihydrobenzofurans, indolines, chromans, indanes, and polycyclic indolines.